2017
DOI: 10.1136/bjophthalmol-2017-311097
|View full text |Cite
|
Sign up to set email alerts
|

Posterior keratoconus

Abstract: Posterior keratoconus (PKC) is a rare, typically non-inflammatory condition that is characterised by an abnormal posterior corneal curvature, which may be accompanied by overlying stromal opacification. It is usually congenital and can be associated with other ocular and systemic abnormalities. PKC remains a clinical diagnosis, although imaging techniques including ultrasound biomicroscopy and anterior segment optical coherence tomography may be useful tools for confirmation and classification. Genetic studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…[ 2 ] There is constellation of posterior segment features quoted in the literature that can occur along with posterior keratoconus with undetermined genetic linkage. [ 3 4 5 6 7 8 ] Our patient had a unique association of bilateral sporadic posterior keratoconus with FEVR, which to our knowledge never reported earlier. Atypical presentation of FEVR with associated retinal detachment and subtle posterior keratoconus makes our case a diagnostic challenge.…”
Section: Discussionsupporting
confidence: 48%
“…[ 2 ] There is constellation of posterior segment features quoted in the literature that can occur along with posterior keratoconus with undetermined genetic linkage. [ 3 4 5 6 7 8 ] Our patient had a unique association of bilateral sporadic posterior keratoconus with FEVR, which to our knowledge never reported earlier. Atypical presentation of FEVR with associated retinal detachment and subtle posterior keratoconus makes our case a diagnostic challenge.…”
Section: Discussionsupporting
confidence: 48%
“…The PKC is usually congenital and can be associated with other ocular and systemic abnormalities, such as microcornea, synechiae, corectopia, anterior polar cataract, and so on [ 6 ]. The trauma has been sporadically proposed as an important cause of acquired PKC, as are an oblique penetrating injury leading to posterior lamellar splitting, destruction of the posterior surface, and keratohematoma [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that the histologic features of SND include attenuated epithelium, disruption of the Bowman layer, fibroblast overgrowth, and deposition of the extracellular matrix [ 3 5 ]. Posterior keratoconus (PKC) is a rare corneal developmental anomaly characterized by an entire or localized abnormality of the posterior corneal surface [ 6 ]. Also, cases acquired after trauma have been reported [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bilateral corneal opacities, increased localized central posterior corneal curvature, amblyopia, and a history of strabismus surgery before age 5 in this 40-year-old woman point to a clinical diagnosis of congenital posterior keratoconus (keratoconus posticus circumscriptus with central–paracentral involvement). 1 Complete ocular and systemic examination is a must to rule out coexisting abnormalities. Normal irides and gonioscopy imply lack of iridocorneal adhesions and angle abnormalities.…”
Section: Soosan Jacob Ms Frcs Dnbmentioning
confidence: 99%
“…The most likely diagnosis of this patient is posterior keratoconus. 1–3 The Pentacam images show posterior steepening and the anterior segment OCT shows posterior corneal curvature abnormality. This condition is considered an anterior segment dysgenesis disorder and may be associated with systemic findings such as genitourinary abnormalities as in this case.…”
Section: Natalie Afshari MD Facsmentioning
confidence: 99%